Molecular cloning and subcellular localization of six HDACs and their roles in response to salt and drought stress in kenaf (Hibiscus cannabinus L.) - Wei, Fan (Biol Res, 2019)
BACKGROUND: Histone acetylation is an important epigenetic modification that regulates gene activity in response to stress. Histone acetylation levels are reversibly regulated by histone acetyltransferases (HATs) and histone deacetylases (HDACs). The imperative roles of HDACs in gene transcription, transcriptional regulation, growth and responses to stressful environment have been widely investigated in Arabidopsis. However, data regarding HDACs in kenaf crop has not been disclosed yet. RESULTS: In this study, six HDACs genes (HcHDA2, HcHDA6, HcHDA8, HcHDA9, HcHDA19, and HcSRT2) were isolated and characterized. Phylogenetic tree revealed that these HcHDACs shared high degree of sequence homology with those of Gossypium arboreum. Subcellular localization analysis showed that GFP-tagged HcHDA2 and HcHDA8 were predominantly localized in the nucleus, HcHDA6 and HcHDA19 in nucleus and cytosol. The HcHDA9 was found in both nucleus and plasma membranes. Real-time quantitative PCR showed that the six HcHDACs genes were expressed with distinct expression patterns across plant tissues. Furthermore, we determined differential accumulation of HcHDACs transcripts under salt and drought treatments, indicating that these enzymes may participate in the biological process under stress in kenaf. Finally, we showed that the levels of histone H3 and H4 acetylation were modulated by salt and drought stress in kenaf. CONCLUSIONS: We have isolated and characterized six HDACs genes from kenaf. These data showed that HDACs are imperative players for growth and development as well abiotic stress responses in kenaf. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40659-019-0227-6) contains supplementary material, which is available to authorized users.